Študij dela in ergonomija: Navodila za vaje - Vujica Herzog, Nataša (2020)
Work Study and Ergonomics: Instructions for Exercises. In practice ergonomics workplace design is usually performed in two steps. First step is observing workplace and worker to determine basic working characteristics and study possible worker's problems. In the next step metric analyses of workplace are performed to define environmental impact on worker. We measure temperature, humidity, air velocity, illumination and noise. Beside these measures also metabolism is calculated and detailed analysis of worker’s movements is performed. Analysis of worker’s movements can be performed manually or with computer aided ergonomics software e.g. Siemens package Jack. Jack is a complete system for generating 3D environments and interacting with them in a powerful graphical environment. We can insert human model into this 3D environment, make simulation of human movements at work and check the suitability of performed movements with different ergonomics analyses. In this manual different cases from real environment are presented and use of ergonomic analyses for effective workplace design.
Keywords: ergonomics; ergonomics workplace design; workplace analyses; measuring enwironmental conditions; ergonomics analyses